2023
DOI: 10.3389/fpls.2023.1179701
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of heat, drought, and combined heat–drought stress on yield, phenotypic traits, and gluten protein traits: capturing stability of spring wheat in excessive environments

Abstract: Wheat production and end-use quality are severely threatened by drought and heat stresses. This study evaluated stress impacts on phenotypic and gluten protein characteristics of eight spring wheat genotypes (Diskett, Happy, Bumble, SW1, SW2, SW3, SW4, and SW5) grown to maturity under controlled conditions (Biotron) using RGB imaging and size-exclusion high-performance liquid chromatography (SE-HPLC). Among the stress treatments compared, combined heat–drought stress had the most severe negative impacts on bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…no relationship between the stability and TKW was found among durum wheat genotypes Lama et al (2023). reported that some spring wheat genotypes with the highest stability had the lowest mean values for TKW.The results of TW, opposite to PC, showed increasing stability as the level of TW increased.…”
mentioning
confidence: 91%
“…no relationship between the stability and TKW was found among durum wheat genotypes Lama et al (2023). reported that some spring wheat genotypes with the highest stability had the lowest mean values for TKW.The results of TW, opposite to PC, showed increasing stability as the level of TW increased.…”
mentioning
confidence: 91%